Assessment of lead exposure among the workers in a storage battery factory [Bi̇r akü fabri̇kasinda çalişan i̇şçi̇lerde kurşun maruzi̇yeti̇ni̇n deǧerlendi̇ri̇lmesi̇] - (:unkn) unknown (My University, 2007)
Objective: In this study we aimed to determine the health effects of lead exposure and assess the lead intoxication in battery production plant workers. Material and Methods: Fifty-six workers accepted to participate in the study. A structured questionnaire was given to evaluate the symptoms, and blood samples were collected for laboratory analyses. Blood lead concentration (B-Pb) was studied by ICP-MS method to assess the lead exposure. Results: The median of B-Pb concentration was 46mg/dL among the workers in lead production departments. Sixty nine percent of all the workers and 89,7% of the workers in lead production departments had lead intoxication. Seventy nine percent of the workers had at least one symptom related to lead exposure. There was no relationship between age, exposure time and smoking. Conclusion: In conclusion, the results indicated that the workers have a high lead intoxication risk in battery production plants. In this study, extremely high levels of B-Pb were recorded. These levels were higher than the levels that have been reported in similar studies. This significantly high intoxication rate at the battery factory can be explained by the inadequacy of the environmental measures and lack of periodical controls and treatment of the workers.
Keywords: Environmental exposure; Lead intoxication; Occupational health; Storage battery workers